2020
DOI: 10.3390/molecules25133022
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Silver Nanoparticles: Assessment of Their Cytotoxicity, Genotoxicity and Study of Capping Proteins

Abstract: The development of nanotechnology in the last two decades has led to the use of silver nanoparticles (AgNPs) in various biomedical applications, including antimicrobial, anti-inflammatory, and anticancer therapies. However, the potential of the medical application of AgNPs depends on the safety of their use. In this work, we assessed the in vitro cytotoxicity and genotoxicity of silver nanoparticles and identified biomolecules covering AgNPs synthesized from actinobacterial strain SH11. The cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 75 publications
2
28
0
Order By: Relevance
“…The AgNPs colloidal solutions with pH value of 5.94 were measured. Silver nanoparticles (AgNPs) had average hydrodynamic diameters of 101.13 ± 0.85 nm with low polydispersity index (PDI) value (0.20 ± 0.01 nm), indicating high particle homogeneity [ 23 ] ( Figure 2 a) and the zeta potential value of -47.63 ± 5.79 mV revealed the stability and negatively charge of AgNPs [ 24 ] ( Figure 2 b). This zeta potential value indicated that tannic acid contributed to the negative charge distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AgNPs colloidal solutions with pH value of 5.94 were measured. Silver nanoparticles (AgNPs) had average hydrodynamic diameters of 101.13 ± 0.85 nm with low polydispersity index (PDI) value (0.20 ± 0.01 nm), indicating high particle homogeneity [ 23 ] ( Figure 2 a) and the zeta potential value of -47.63 ± 5.79 mV revealed the stability and negatively charge of AgNPs [ 24 ] ( Figure 2 b). This zeta potential value indicated that tannic acid contributed to the negative charge distribution.…”
Section: Resultsmentioning
confidence: 99%
“…From Dynamic Light Scattering (DLS) measurement, we found that the hydrodynamic diameter of AgNPs was greater than the average size observed from TEM due to the solvent and stabilizer layers present around the AgNPs’ surface [ 34 ]. The negative zeta potential of −43.9 mV ( Figure 2 b) proved the high stability of AgNPs due to the electrostatic repulsion of NPs in the solution [ 24 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in the nanoparticle size and charge might be related to strain specificity, growth conditions of strain, and conditions used during the synthesis process (Kupryashina et al, 2013;Mohanta and Behera, 2014;Rai et al, 2016). Some subtle differences have been observed even in the same isolate (Wypij et al, 2017(Wypij et al, , 2020. The FTIR bands observed in region 3,430 cm −1 is characteristic for vibrations of hydroxyl and amino groups (Shanmugaiah et al, 2015;Qayyum et al, 2017;Wypij et al, 2018a;Oves et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The AgNPs synthesized by peel extract of Citrus sinensis were capped by three different proteins with aspartic-type endopeptidase, GSH S-transferase, and oxalate oxidase activities (Barros et al, 2018). Recently, Wypij et al (2020) separated proteins associated with AgNPs from actinobacteria using SDS-PAGE and found three protein bands that showed the highest homology to porins previously described in Gramnegative bacteria. Similarly, in the present work SDS-PAGE analysis showed the presence of five proteins bands at a molecular weight between 31.7 and 280.9 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, silver is reported for its ability to reduce infections in the treatment of burned areas [ 37 ]. When silver is prepared as nanoparticles, it provides excellent antimicrobial effects [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%